The Association Between Sugar-Sweetened Beverage Consumption and Toddler's Diarrhea: A Systematic Review - Aferita Sari; Aprilliana Risma Nugrahella (The International Journal of Medical Science and Health Research, 2025)
Introduction: Toddler's diarrhea, or Chronic Nonspecific Diarrhea of Childhood (CNSD), is a common functional gastrointestinal disorder in children aged 6 months to 5 years. It is characterized by chronic, loose stools in otherwise healthy, thriving children. While dietary factors are implicated, particularly fruit juice, a comprehensive synthesis of the evidence across all types of sugar-sweetened beverages (SSBs) is lacking. This systematic review aims to evaluate the association between SSB consumption and toddler's diarrhea. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for studies published in English. Randomized controlled trials (RCTs), controlled trials, cohort studies, case-control studies, and case series (N≥5) evaluating the association between SSB (including fruit juices, sodas, and other sweetened drinks) consumption and diarrheal outcomes in children aged 6 months to 5 years were included. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Methodological quality was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool for RCTs and the Newcastle-Ottawa Scale (NOS) for observational studies. Findings were synthesized narratively. Results: Seventeen studies, comprising six RCTs/controlled trials, six observational studies, and five case series, met the inclusion criteria. The evidence consistently demonstrated a strong association between the consumption of SSBs and toddler's diarrhea. An RCT found that infants consuming apple juice or white grape juice had significantly higher fecal output (3.94 g/kg/h and 3.59 g/kg/h, respectively) and longer diarrhea duration (49.4 hours and 47.5 hours, respectively) compared to those consuming water (2.19 g/kg/h and 26.5 hours) (Valdovinos et al., 2005). Observational studies linked excessive fluid intake, particularly from juice, to increased stool frequency (4-10 stools/day) (Greene and Ghishan, 1983). Breath hydrogen tests confirmed carbohydrate malabsorption (fructose and sorbitol) as a key mechanism (Hyams and Leichtner, 1985; Smith and Lifshitz, 1995). Dietary intervention studies showed that restricting or eliminating SSBs was curative or led to significant symptom resolution in most cases (Hyams and Leichtner, 1985). Beverages with a high fructose-to-glucose ratio and sorbitol content, such as apple and pear juice, were most frequently implicated (Gormally et al., 1997). Discussion: The findings support a multifactorial pathophysiological model where the high osmotic load from poorly absorbed sugars (fructose, sorbitol) in SSBs exceeds the absorptive capacity of a toddler's immature gut. This effect is often compounded by rapid intestinal transit from low-fat diets and high overall fluid volume. The mechanistic principles derived from studies on fruit juice can be logically extended to other SSBs sweetened with high-fructose corn syrup. While some evidence supports dilute juice for rehydration in mild acute gastroenteritis due to palatability, its role is distinct from its causal contribution to chronic functional diarrhea (Freedman et al., 2016). Conclusion: There is strong evidence to support a causal association between the consumption of SSBs and the etiology of toddler's diarrhea. A detailed dietary history focusing on SSB intake is the cornerstone of diagnosis, and dietary modification is the primary, most effective management strategy.